Visual Imagery and Human Rights Practice (Global Transformations in Media and Communication Research - A Palgrave and IAMCR Series, 2018)
Visual Imagery and Human Rights Practice examines the interplay between images and human rights, addressing how, when, and to what ends visuals are becoming a more central means through which human rights claims receive recognition and restitution. The collection argues that accounting for how images work on their own terms is an ever more important epistemological project for fostering the imaginative scope of human rights and its purchase on reality. Interdisciplinary in nature, this timely volume brings together voices of scholars and practitioners from around the world, making a valuable contribution to the study of media and human rights while tackling the growing role of visuals across cultural, social, political and legal structures.